Taymāʼ. - Macdonald, M. C. A., (Taymāʼ, multidisciplinary series on the results of the Saudi-German Archaeological Project., 2020)
The Catalogue contains all inscriptions discovered during 24 seasons of Saudi-German excavations at Taymāʼ, 2004-15. The 113 objects carry inscriptions in different languages and scripts, including Babylonian cuneiform, Imperial Aramaic inscriptions, Arabic inscriptions and more, illustrating the linguistic diversity of the oasis through time.